Faktor-faktor yang mempengaruhi produksi padi gogo di Kecamatan Cikalong Kabupaten Tasikmalaya - Hasanudin, Sansan; Hidayati, Reny; Sundari, Ristina Siti (Universitas Musamus, Merauke, Papua, 2024)
Drought is a direct impact on the agricultural sector that causes dry land due to drought or rice scarcity. The solution for farmers in agriculture is to plant drought-resistant rice, namely upland rice. Objective To determine the factors that affect upland rice production in Cikalong District, Tasikmalaya Regency. Methods This study uses a survey method, with the data used in this study being quantitative data. Results The most significant variable among the factors affecting upland rice production in Cikalong District, Tasikmalaya Regency, is land area (X1), as the sig value is 0.064 < 0.10 with α = 10%, making land area the only factor that influences production. Conclusion The factors affecting production in Cikalong District, Tasikmalaya Regency, simultaneously are land area, seeds, labor, and fertilizer, which significantly influence the increase in upland rice production in Cikalong District, Tasikmalaya Regency. Suggestion: Future authors are expected to expand new research based on these findings so that other production factors that have not been measured can be studied to improve quality and utility.